Voluntourism and the Sustainable Development Goals - Devereux, Peter; Holmes, Kirsten (Goodfellow publishers, 2018)
This chapter begins by reviewing how voluntourism practice and research has evolved over the past nearly two decades. Next, the chapter identifies the potential relationships between voluntourism and the Sustainable Development Goals (SDGs). Following on from this analysis the chapter considers how voluntourism can contribute to achieving the SDGs, identifying collaborative opportunities for voluntourism practice to support long term sustainable development both in low, middle and high income countries.